176k views
3 votes
If h (x)=√49-x², find h (0), h (-7) and h (9).​

User Mshildt
by
4.8k points

1 Answer

5 votes

Answer:

Explanation:

f(0) = √49 - x^2

f(0) means that wherever you see an x on the right, you put a zero.

so f(0) = √49 - 0^2

f(0) = √49

f(0) = 7

f(-7) = √49 - x^2

Again the meaning is that where you see an x on the right, you substitute - 7 for that x.

f(-7) = √49 - (-7)^2

f(-7) = 7 - 49

f(-7) = - 42

f(9) = √49 - (9)^2

f(9) = 7 - 81

f(9) = - 74

User Manasi
by
4.5k points